Cultural Determinants Associated with Malnutrition in Children Aged 6-59 Months in West Pokot County, Kenya - Anthony Kipkoech Koross; Gordon Nguka; Everlyne Morema (Preventive Care in Nursing and Midwifery Journal, 2023)
Background: Malnutrition is deficiencies or excess nutrients by an individual. Includes under-nutrition and micronutrient-related malnutrition. It causes about half of all fatalities in children below five years; increases the chance of a child dying from common ailments. Cultural determinants are associated with malnutrition of ages 6-59 months. Objectives: The study sought to establish the determinants contributing to child malnutrition in West Pokot County of Kenya. Methods: This was cross sectional study. Multistage cluster sampling was applied. Anthropometric measures of 420 children aged 6-59 months in Pokot North Sub-County were assessed. Data was collected from August-September, 2022 using online questionnaire. Pretesting was done for validity and reliability. SPSS v.2022 used for data analysis. Chi-Square and Odds Ratios and Confidence intervals were used to test variables. Results: Mean (SD) age of the respondents’ children was 29.9 (16.0). Over 60% of children were below 35 weeks. Children with 0-11 months had lower representation (15.2%). 82.4% had one younger sibling. Monogamy (76.8%) had fewer malnutrition cases (OR: 0.5; P=0.015). Violence was high and had impact on malnutrition (34.5%). Traditional food restrictions caused malnutrition (OR:1.8; 95% CI:1.2-2.8; P=0.006). Conclusion: There is evidence that some cultural aspects: types of marriage, caretaker violence and food taboos contribute to malnutrition in children aged 6-59 months in West Pokot County. Awareness on harmful cultural practices should be implemented. More studies should be done to establish why cultural practices still exist.